2019
DOI: 10.4236/ojps.2019.91010
|View full text |Cite
|
Sign up to set email alerts
|

Decentralized Governance in the Management of Urban Health Care Systems in Developing Countries

Abstract: Enhanced Health care services address not only one of the key Sustainable Development Goals (SDG) which is goal No 3, but also the development strategies for most developing countries. Good governance is critical to improving health care systems. Many developing countries therefore have decentralized health care systems as a way of improving good governance and as a means of attaining improved access to and delivering quality health care services to both urban and rural population. Decentralization involves th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2020
2020
2021
2021

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 8 publications
0
6
0
Order By: Relevance
“…As awareness would likely improve with the enactment of child laws, Oman would need to avoid the difficulty that has persisted in other societies in transition where the services and amenities for victims are located entirely in urban areas (Obosi 2019 ). While laws and policies are best evolved in a centralized manner, most implementation – except tertiary care – need to be decentralized, and made region – and subculture-specific.…”
Section: Distribution Of Servicesmentioning
confidence: 99%
“…As awareness would likely improve with the enactment of child laws, Oman would need to avoid the difficulty that has persisted in other societies in transition where the services and amenities for victims are located entirely in urban areas (Obosi 2019 ). While laws and policies are best evolved in a centralized manner, most implementation – except tertiary care – need to be decentralized, and made region – and subculture-specific.…”
Section: Distribution Of Servicesmentioning
confidence: 99%
“…Indeed, studies have shown higher rates of unauthorized payments in countries with more tiers of government (Fan et al, 2009). Further, research has shown that the large information asymmetry between providers and patients, and the complexities that arise when payers' incentives diverge from both providers and clients, all conspire to make healthcare systems particularly susceptible to payment irregularities and inefficiencies (Mostert et al, 2015;Vian, 2008). It is notoriously difficult to determine what counts as unauthorized or irregular in a complex system where opportunities to request payments can exist from the systemic and institutional levels down to the level of the individual, making it notoriously difficult to define (Johnston, 1996).…”
Section: Regulatory Complexitymentioning
confidence: 99%
“…A fundamental challenge for health systems is the need to adapt to changes in the structure of health service needs, technological advances, and the economic and institutional environment of healthcare providers]. Health systems are most e cient when they combine both centralization and decentralization functions [5,6,7]. The medicine is one of the most humanistic and auspicious eld of human activity with rapidly expanding new diagnostic and therapeutic modalities and with highly trained specialists to deliver both the science and art of medicine.…”
Section: Introductionmentioning
confidence: 99%